2017
DOI: 10.1016/j.pedhc.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Hospice Use for Infants With Life-Threatening Health Conditions, 2007 to 2010

Abstract: Background Infant deaths account for a majority of all pediatric deaths. However, little is known about the factors that influence parents to use hospice care for their infant with a life- threatening health condition. Methods Data were used from the 2007 to 2010 California Medicaid claims files (n=207). Analyses included logistic and negative binomial multivariate regression models. Results Over 15% of infants enrolled in hospice care for an average of 5 days. Infant girls and infants with congenital anom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Others have drawn similar conclusions among this age-group at end of life. 7,18,33 One possible reason for the increase in days of hospice enrollment may reflect new end-of-life care delivery models for infants. Perinatal hospice and palliative care is an option for families who discover during pregnancy that their infant has a life-limiting condition but choose to continue the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have drawn similar conclusions among this age-group at end of life. 7,18,33 One possible reason for the increase in days of hospice enrollment may reflect new end-of-life care delivery models for infants. Perinatal hospice and palliative care is an option for families who discover during pregnancy that their infant has a life-limiting condition but choose to continue the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that a child's age, sex, and place of residence influence utilization of end-of-life care including hospice utilization, primary care visits, hospital admission, and emergency department (ED) visits. 9,[16][17][18] Enablers such as type of insurance have also been related to end-of-life care for children, 9,12,13,16 while the health of the child has been shown to be a critical driver of utilization and costs of care. 7,9,16 Thus, this framework suggests that predisposing, enabling, and need factors are potential considerations when examining health utilization and spending among commercially insured children at end of life.…”
mentioning
confidence: 99%
“…Previous reports have demonstrated that many states have a robust network of primary care practitioners to offer additional support to Medicaid patients with chronic illnesses, 18,23,36,43 so it is not surprising that this trend would also be evident among those with life-limiting diagnoses. Primary care providers may be able to offer offer an additional layer of support through comprehensive symptom-based management, spiritual assessments, discussions surrounding goals of care, and advance care planning (ACP).…”
Section: Discussionmentioning
confidence: 99%
“…The third measure, hospice length of stay , was operationalized as a daily count of outpatient hospice care encounters in the last year of life. 36 Daily counts of hospice length of stay were derived from the per diem payments to hospice using the MAX Other Services hospice revenue codes.…”
Section: Methodsmentioning
confidence: 99%
“…Our concern, based on extensive work with pediatric secondary and claim-based data sets, is that a significant number of very young children might be excluded from palliative and endof-life studies because they are not classified with a CCC. 14,15,17 Understanding whether the CCC classification system applies to infants is critical in advancing the science of palliative and end-of-life care. 18 Given that over half of the children who die each year in the United States are infants, 19 ensuring an effective method of identifying these very young children in research will reduce bias and improve the reliability of our findings.…”
Section: Introductionmentioning
confidence: 99%